2017
DOI: 10.1002/jbio.201700038
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level light emitting diode therapy promotes long–term functional recovery after experimental stroke in mice

Abstract: We aimed to investigate the effects of low-level light emitting diode therapy (LED-T) on the long-term functional outcomes after cerebral ischemia, and the optimal timing of LED-T initiation for achieving suitable functional recovery. Focal cerebral ischemia was induced in mice via photothrombosis. These mice were assigned to a sham-operated (control), ischemic (vehicle), or LED-T group [initiation immediately (acute), 4 days (subacute) or 10 days (delayed) after ischemia, followed by once-daily treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Recently, phototherapy with light-emitting diode (LED) has been used for tissue repair with many protective effects, such as inhibiting inflammatory response and increasing collagen synthesis [9]. In an experimental ischemic stroke model, LED therapy attenuated neuroinflammatory responses and inhibited microglial activation, thus generating a smaller infarct size [10]. Therefore, we hypothesize that LED therapy might reduce VA inducibility by attenuating microglial and sympathetic activation after myocardial I/R.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phototherapy with light-emitting diode (LED) has been used for tissue repair with many protective effects, such as inhibiting inflammatory response and increasing collagen synthesis [9]. In an experimental ischemic stroke model, LED therapy attenuated neuroinflammatory responses and inhibited microglial activation, thus generating a smaller infarct size [10]. Therefore, we hypothesize that LED therapy might reduce VA inducibility by attenuating microglial and sympathetic activation after myocardial I/R.…”
Section: Introductionmentioning
confidence: 99%
“…PBM, including LED and low-level laser therapy, is the low power (1-500 mW) nonthermal delivery of photons that induces a beneficial biological response in cells and tissues, 40 such as stroke 16 and traumatic brain injury. 13 PBM has been increasingly used for treatment of neuroinflammation 15 and neurodegenerative diseases.…”
Section: Led Therapy For Post-ami Vas and Neuroimmune Modulationmentioning
confidence: 99%
“…Recently, studies have shown that LED therapy might inhibit activation of microglia and increase the level of brainderived neurotrophic factor, thereby resulting in a smaller infarct size in experimental ischemic stroke. 16 Furthermore, LED therapy might attenuate inflammasomes and reduce the expression of the proinflammatory cytokines IL-1β and IL-18 in a brain ischemic stroke model. 15 In our study, we also found that LED therapy significantly attenuated inflammation, microglial activation, and AMI-induced LSG neural activation.…”
Section: Led Therapy For Post-ami Vas and Neuroimmune Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, previous studies have shown that both M2 microglia and BDNF exert antineuroinflammatory effects [ 11 14 ]. Furthermore, LED therapy has been widely used in neurological and brain injury treatment [ 15 , 16 ]. Moreover, studies have shown that LED therapy might increase M2 microglia and BDNF in the brain, thereby decreasing the ischemic stroke injury [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%